Excitonic enhancement of nonradiative energy transfer from a quantum well in the optical near field of energy gradient quantum dots - Nizamoglu, Sedat (2013)
We report strong exciton migration with an efficiency of 83.3% from a violet-emitting epitaxial quantum well (QW) to an energy gradient colloidal construct of layered green- and red-emitting nanocrystal quantum dots (NQDs) at room temperature, enabled by the interplay between the exciton population and the depopulation of states in the optical near field. Based on the density matrix formalization of near-field interactions, we theoretically model and demonstrate that the energy gradient significantly boosts the QW-NQDs exciton transfer rate compared to using mono-dispersed NQDs, which is in agreement with the observed experimental results.